Pulse pressure is independently associated with carotid plaque ulceration. - Lovett, J; Howard, S; Rothwell, P (2003)
BACKGROUND: Plaque rupture is the principal cause of acute coronary ischaemia, and unstable carotid plaques are associated with a high risk of ischaemic stroke. Carotid plaque ulceration also predicts acute coronary events, suggesting that systemic factors may determine plaque instability. One potentially important factor is pulse pressure. There is indirect evidence that cyclical haemodynamic forces affect plaque stability, and pulse pressure is a strong predictor of coronary events. OBJECTIVE: To study the association between pulse pressure and plaque ulceration. DESIGN AND METHODS: We studied angiograms from 3007 patients with recently symptomatic carotid stenosis in the European Carotid Surgery Trial. Presence of ulceration was related to the different components of blood pressure [pulse pressure, systolic blood pressure (SBP), mean arterial pressure (MAP), and diastolic blood pressure (DBP)], and adjustment was made for age, sex, diabetes, smoking, and the degree of vessel stenosis. RESULTS: Pulse pressure was the strongest independent predictor of ulceration of the symptomatic carotid plaque [adjusted odds ratio (OR) for the upper compared with the lower quintile 2.07, 95% confidence interval (CI) 1.25 to 3.44; P = 0.004]. This relationship was weaker for SBP (OR 1.66, 95% CI 1.05 to 2.62; P = 0.02), and non-significant for MAP (OR 1.58, 95% CI 1.01 to 2.48, P = 0.13) and DBP (OR 1.67, 95% CI 0.73 to 1.87, P = 0.50). CONCLUSIONS: Pulse pressure is independently associated with carotid plaque ulceration, supporting the hypothesis that pulsatile haemodynamic forces are an important cause of plaque rupture.